Bioenergy production and utilization in different sectors in Sweden: A state of the art review - Stephen O. Amiandamhen; Anuj Kumar; Stergios Adamopoulos; Dennis Jones; Bengt Nilsson (BioResources, 2020)
In the continual desire to reduce the environmental footprints of human activities, research efforts to provide cleaner energy is increasingly becoming vital. The effect of climate change on present and future existence, sustainable processes, and utilizations of renewable resources have been active topics within international discourse. In order to reduce the greenhouse gases emissions from traditional materials and processes, there has been a shift to more environmental friendly alternatives. The conversion of biomass to bioenergy, including biofuels has been considered to contribute to the future of climate change mitigation, although there are concerns about carbon balance from forest utilization. Bioenergy accounts for more than one-third of all energy used in Sweden and biomass has provided about 60% of the fuel for district heating. Apart from heat and electricity supply, the transport sector, with about 30% of global energy use, has a significant role in a sustainable bioenergy system. This review presents the state of the art in the Swedish bioenergy sector based on literature and Swedish Energy Agency’s current statistics. The review also discusses the overall bioenergy production and utilization in different sectors in Sweden. The current potential, challenges, and environmental considerations of bioenergy production are also discussed.